Investigation of Multi-layered coating on Tribological property during boring process. (2021) - Lawrance, G.; Sam Paul, P.; Shaji, Jeffrey; Sudhagar, P. Edwin; Samuel Ratna Kumar, P.S.
Abstract: In boring process, due to rise in temperature at cutting zone, the tool is subjected to excess wear, which also affects the production rate, product quality and economy rate. A multilayer coated tools as a positive approach towards the tribology property such as tool wear, especially at high cutting velocities. In the present investigation, the boring tool is coated with varied oxides such as aluminium, titanium and zirconium using spray, spin and dip coating technique and cutting experiments were conducted on wet, semisolid and dry condition. A 27 run cutting experiments were conducted based on the taguchi technique and it was found that titanium and zirconium oxides with spray coating and wet condition afford promising results.